It’s a Whole New Dating World in the 2020s: Exploring Online Dating Today - Tadros, Eman; Jordan, Jessica Love; Sugrue, Kathryn (Utan Kayu Publishing, 2024)
This conceptual article provides a comprehensive overview of the historical evolution of dating practices from the 19th century to the present day, exploring the influence of social, cultural, and technological factors on dating. The impact of the COVID-19 pandemic and the consequent rise of dating apps and virtual dating in the 2020s is also examined. The article also discusses the risks and red flags associated with online dating, including scams and harassment, and provides guidelines for maintaining safety while using dating apps. This information to showcase the need for further investigation into the complexities of modern-day dating practices. The findings highlight the need for a deeper understanding of the complexities of current dating practices and further research on the implications of changing dating practices on social relationships and well-being.